Insight into the Structural Features of Pyrazolopyrimidine‐ and Pyrazolopyridine‐based B‐RafV600E Kinase Inhibitors by Computational Explorations. (20th March 2014) - Li, Yan; Han, Chunxiao; Wang, Jinghui; Yang, Yinfeng; Zhang, Jingxiao; Zhang, Shuwei; Yang, Ling
<x xml:space="preserve">Abstract</x> Presently, both ligand‐based and receptor‐based 3D‐QSAR modelings were performed on 107 pyrazolopyrimidine‐ and pyrazolopyridine‐based inhibitors of B‐RafV600E kinase. The optimal model is successful to predict the inhibitors' activity with Q2 of 0.504, R2ncv of 0.960, and R2pred of 0.872. Besides, the 3D contour maps explain well the structural requirements of the interaction between the ligand and the receptor. Furthermore, molecular docking and MD were also carried out to study the binding mode. Our findings are the following: (i) Bulky substituents at position 3, 10 and ring D improve the inhibitory activity, but impair the activity at position 5, 11, and 19. (ii) Electropositive groups at position 10, 13 and 20 and electronegative groups at position 2 increase the biological activity. (iii) Hydrophobic substituents at ring C are beneficial to improve the biological activity, while hydrophilic substituents at position 11 and ring D are good for the activity. (4) This scaffold of inhibitors may bind to the B‐Raf kinase with an 'L' conformation and belong to type III binding mode, which is fixed by hydrophobic interaction and hydrogen bonds with residues from hinge region and DFG motif. These results may be a guidance to develop new B‐RafV600E kinase inhibitors.